Intraventricular Tissue Plasminogen Activator and Shunt Dependency in Aneurysmal Subarachnoid Hemorrhage Patients With Cast Ventricles. Issue 6 (30th August 2021) - Catapano, Joshua S; Rumalla, Kavelin; Karahalios, Katherine; Srinivasan, Visish M; Labib, Mohamed A; Cole, Tyler S; Baranoski, Jacob F; Rutledge, Caleb; Rahmani, Redi; Jadhav, Ashutosh P; Ducruet, Andrew F; Albuquerque, Felipe C; et al.
Abstract: BACKGROUND: Patients with intraventricular hemorrhage (IVH) are at higher risk of hydrocephalus requiring an external ventricular drain and long-term ventriculoperitoneal shunt placement. OBJECTIVE: To investigate whether intraventricular tissue plasminogen activator (tPA) administration in patients with ventricular casting due to IVH reduces shunt dependence. METHODS: Patients from the Post–Barrow Ruptured Aneurysm Trial (PBRAT) database treated for aneurysmal subarachnoid hemorrhage (aSAH) from August 1, 2010, to July 31, 2019, were retrospectively reviewed. Patients with and without IVH were compared. A second analysis compared IVH patients with and without ventricular casting. A third analysis compared patients with ventricular casting with and without intraventricular tPA treatment. The primary outcome was chronic hydrocephalus requiring permanent shunt placement. RESULTS: Of 806 patients hospitalized with aSAH, 561 (69.6%) had IVH. IVH was associated with a higher incidence of shunt placement (25.7% vs 4.1%, P < .001). In multivariable logistic regression analysis, IVH was independently associated with increased likelihood of shunt placement (odds ratio [OR]: 7.8, 95% CI: 3.8-16.2, P < .001). Generalized ventricular casting was present in 80 (14.3%) patients with IVH. In a propensity-score adjusted analysis, generalized ventricular casting was an independent predictor of shunt placement (OR: 3.0, 95% CI: 1.8-4.9, P < .001) in patients with IVH. Twenty-one patients with ventricular casting received intraventricular tPA. These patients were significantly less likely to require a shunt (OR: 0.30, 95% CI: 0.010-0.93, P = .04). CONCLUSION: Ventricular casting in aSAH patients was associated with an increased risk of chronic hydrocephalus and shunt dependency. However, this risk decreased with the administration of intraventricular tPA.